Structural unemployment after the crisis in Austria - Michael Christl; Monika Köppl-Turyna; Dénes Kucsera (IZA Journal of European Labor Studies, 2016)
This paper analyzes the Austrian Beveridge curve as well as the Beveridge curves for different economic sectors in Austria over the period from 2008 onwards. We find significant outward shifts of the Beveridge curves in eight of the 21 sectors of the economy. We further analyze what factors have contributed to this change. Our results suggest that a significant part of the currently rising unemployment in Austria may be attributed to structural changes. Those structural changes mainly affect the four large sectors: construction, wholesale, transportation, and accommodation and food service activities.
Keywords: J62; J63; E24; E32; 330; Beveridge curve; Crisis; Mismatch; Structural unemployment